Capturing the ineffable : an anthropology of wisdom - Kao, Philip; Alter, Joseph S. (University of Toronto Press, 2020)
"Wisdom is peculiarly abstract, ineffable, and yet perennial. It is also temporal, stretching forwards as well is backwards in time. Wisdom is often treated as the outcome of life experience, reflection, discipline, and equanimity. Capturing the Ineffable aims to establish wisdom as an area if inquiry within anthropology and an analytic account of wisdom and its role and focus in anthropology. In addition to developing theories for an anthropology (and excavation) of wisdom, this volume argues collectively that anthropology is especially well suited to engage in questioning what it is that is called wisdom, and how wisdom, as a concept, and an enacted activity, functions in metaphysical and interpersonal experiences, values, and judgements. The contributors include many key US and UK thinkers."--